Jornal A Imprensa como fonte de informação e memória da produção editorial paraibana no século XX (1912 a 1942). - Costa, Suzana Queiroga da (2011)
The present study analyses the editorial production in Paraíba State in the period from 1912 to 1942, specially the production which is found in the literary columns entitled Bibliographia (Bibliography), Livro e Livros Novos (Book and New books) which were issued on the doctrinaire and informative Newspaper << A Imprensa >> established on May, the 27th, 1897 by the first bishop and archbishop in Paraíba State Dom Adaucto Miranda Henriques. A theoretical and methodological plan was adopted as a documentary research in the perspective of Aróstegui (2006), still associated with the theoretical precepts of Cultural History and with its interrelationship with Information Science. The research took as an analytical corpus four hundred and eight authors mainly male of Brazilian nationality in which they presented five hundred and thirty-four titles issued in their majority by Brazilian publishers, prevailingly the literary type. In respect to that we concluded that the newspapers are sources of information and memory of editorial production in Paraíba State and then we concluded the composition of this first edition. Notwithstanding, it s obvious that studying the newspaper << A Imprensa>> (The Press), seeking to understand its plots means realizing it as means of information and memory of the editorial production in Paraíba State, enabling in this way to understand the meanders of the production, circulation and advertising of literary works.